ATIENZA, M. (2022). Sobre la dignidad humana. Madrid: Trotta. - Ramos Pozón, Sergio (Daimon Revista Internacional de Filosofia, 2024)
Reseña de: ATIENZA, Manuel (2022). Sobre la dignidad humana. Madrid: Trotta.